2018
DOI: 10.3389/fphys.2018.00366
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Tolerance in Teleosts: Implications of Cardiac Nitrosative Signals

Abstract: Changes in environmental oxygen (O2) are naturally occurring phenomena which ectotherms have to face on. Many species exhibit a striking capacity to survive and remain active for long periods under hypoxia, even tolerating anoxia. Some fundamental adaptations contribute to this capacity: metabolic suppression, tolerance of pH and ionic unbalance, avoidance and/or repair of free-radical-induced cell injury during reoxygenation. A remarkable feature of these species is their ability to preserve a normal cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 153 publications
(196 reference statements)
1
31
0
Order By: Relevance
“…In several fish species, the resistance to protracted hypoxia/anoxia is supported by a preserved cardiac activity and autonomic cardiovascular control [ 7 , 8 , 9 ]. This allows them not only to mobilize glucose from hepatic glycogen stores to all tissues, but also to transport lactate to the muscle, where it is converted into the less harmful ethanol, rapidly removed via the branchial epithelium [ 10 , 11 ]. In this context, our previous studies have documented that under acute hypoxia, the goldfish improves its cardiac performance [ 12 ], this representing a crucial physiological compensatory mechanism to support its hypoxia tolerance [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several fish species, the resistance to protracted hypoxia/anoxia is supported by a preserved cardiac activity and autonomic cardiovascular control [ 7 , 8 , 9 ]. This allows them not only to mobilize glucose from hepatic glycogen stores to all tissues, but also to transport lactate to the muscle, where it is converted into the less harmful ethanol, rapidly removed via the branchial epithelium [ 10 , 11 ]. In this context, our previous studies have documented that under acute hypoxia, the goldfish improves its cardiac performance [ 12 ], this representing a crucial physiological compensatory mechanism to support its hypoxia tolerance [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The influence elicited by NO on the heart has been widely assessed in mammals, and also in fish, for which many data are now available (see for example [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]). More recently, the role of NO in fish has been extended to the mechanisms which maintain cardiac health under hypoxia (see, for references, [ 10 ]). It has been revealed that, when the NOS activity is compromised by low O 2 , an increased NOS expression and/or a nitrite/nitrate conversion to NO, will stabilize NO levels, and this is protective for the hypoxic myocardium [ 12 , 13 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…To fill this gap in our knowledge, we used the C. auratus heart to (i) evaluate the basal cardiac expression of SELENOT, (ii) ascertain whether exogenous PSELT, encompassing the active redox CXXU motif, affects the performance of the ex vivo isolated and perfused working heart, and (iii) identify the intracellular mechanism activated by PSELT. Moreover, as the goldfish represents a gold standard of hypoxia/anoxia resistance, able to survive at low oxygen levels thanks to a modulation of antioxidant and redox enzyme activity (Lushchak et al, 2001;Gattuso et al, 2018), we investigated whether exposure to acute hypoxia influences the cardiac expression of SELENOT and the response of the goldfish heart to PSELT.…”
Section: Introductionmentioning
confidence: 99%
“…However, the impacts of different hypoxia levels and their effects on fish physiology or behavior is very species-specific (Pollock et al 2007). For example, cyprinid fish, such as the goldfish (Carassius auratus) and the crucian carp (C. carassius), exhibit a striking capacity to survive and remain active for long periods under very low DO, even tolerating anoxia (Gattuso et al 2018). In contrast, DO below 5 mg/L is the threshold for hypoxic stress in salmon (Lucas and Southgate 2003;Olsvik et al 2013;Del Rio et al 2019).…”
mentioning
confidence: 99%